2011
DOI: 10.3233/jad-2011-110650
|View full text |Cite
|
Sign up to set email alerts
|

Memantine Affects Cognitive Flexibility in the Morris Water Maze

Abstract: Alzheimer's disease (AD) is multi-factorial mental disorder characterized by a copious array of congruent features cumulating in disrupted memory and dysthymia. Though the mechanism remains elusive, the highly unspecific pharmaceutical, memantine, provides modest benefits for patients with moderate-to-severe AD. A greater understanding of how memantine affects cognitive function promises to facilitate the search for better therapeutics. We therefore examined cognitive flexibility of mice following 5 and 10 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Similar behavior was also observed in animal studies where only an improvement between the first and the second trial is present in well-trained animals in the DMP or reversal protocol (Garthe et al, 2009; Saab et al, 2011). Despite the observed group differences in the pointing accuracy, the announcement of positional change to our participants was probably responsible for the low group differences in this part of vFGN task.…”
Section: Discussionsupporting
confidence: 73%
“…Similar behavior was also observed in animal studies where only an improvement between the first and the second trial is present in well-trained animals in the DMP or reversal protocol (Garthe et al, 2009; Saab et al, 2011). Despite the observed group differences in the pointing accuracy, the announcement of positional change to our participants was probably responsible for the low group differences in this part of vFGN task.…”
Section: Discussionsupporting
confidence: 73%
“…Administration of memantine has evoked similar effects in both recall trials that validated applied here the step-down avoidance learning protocol in mice as a memory paradigm that is sensitive to a lowaffinity blockade of NMDA receptors. Whilst some labs report memantine-induced cognitive dysfunctions, our data are in line with results obtained in intact mice and rats, which showed beneficial effects of memantine administration at the dose below 10 mg/kg in the active avoidance, water maze, delayed non-match-to-sample task and object recognition tasks without affecting sensomotor functions (Zoladz et al, 2006;Creeley et al, 2008;Minkeviciene et al, 2008;Loskutova and Kostjunina, 2009;Smith et al, 2011;Saab et al, 2011;Ihalainen et al, 2011). The differences in terms of chronicity of training/dosing and motivational impact between the paradigms employed in the studies that showed differential effects of memantine on memory might explain distinct outcomes.…”
Section: Discussionsupporting
confidence: 94%
“…Selection of doses of memantine (1 and 5 mg/kg) and the timing of dosing (single injection 15 min prior to training) were based on previously reported studies, in which memantine induced effects in similar paradigms as employed here (Bachurin et al, 2001;Zoladz et al, 2006;Saab et al, 2011). Preliminary data suggested comparable characteristics of pharmacokinetic between memantine and QXX, which enabled the application of the two drugs with the same dosing regimen .…”
Section: Drug Administrationmentioning
confidence: 97%
“…In addition, a 100-min delay is sufficient to achieve the maximum brain concentration of memantine in the rat [5] , and encompasses commonly chosen pre-experimental intervals in mouse experiments already undertaken with memantine [10][11][12][13][14] .…”
Section: Resultsmentioning
confidence: 99%
“…Acute administration of memantine in the mouse is commonly used as a means to better characterize the in vivo effects of memantine on brain function and behavior [10][11][12][13][14] . However, while memantine pharmacokinetics have been investigated in humans [15] and rats [16] .…”
Section: Introductionmentioning
confidence: 99%